2014
DOI: 10.1088/1741-2560/11/5/056011
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology-based detection of emergency braking intention in real-world driving

Abstract: Our study serves as a real-world verification of the feasibility of electrophysiology-based detection of emergency braking intention as proposed in Haufe et al (2011 J. Neural Eng. 8 056001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 21 publications
2
91
0
Order By: Relevance
“…Concluding, the current findings complement recent studies that have identified correlates of other cognitive processes in realistic driving, including drowsiness [6], [21], [22], [23], emergency braking [9], [24], error-awareness [25], anticipation of self-motivated steering [8] and braking actions [7], as well as visual attention [26]. We purport that future driving assistive systems can exploit information derived from these signals -decoded through a brain-machine interface system-, in combination with information from in-car sensors to tailor the support they provide both to the perceived conditions of the environment as well as the internal state of the driver [27].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Concluding, the current findings complement recent studies that have identified correlates of other cognitive processes in realistic driving, including drowsiness [6], [21], [22], [23], emergency braking [9], [24], error-awareness [25], anticipation of self-motivated steering [8] and braking actions [7], as well as visual attention [26]. We purport that future driving assistive systems can exploit information derived from these signals -decoded through a brain-machine interface system-, in combination with information from in-car sensors to tailor the support they provide both to the perceived conditions of the environment as well as the internal state of the driver [27].…”
Section: Discussionsupporting
confidence: 84%
“…after 400 ms). A decrease in the beta power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is also clear in these two electrodes, appearing at about 300 ms, continuing during lane change behavior. In addition, a late increase at about 500 ms can be observed in the low frequency (1-4 Hz) activity in FCz.…”
Section: Power Spectral Densitymentioning
confidence: 98%
“…Currently, driving assistant systems are mainly based on monitoring the vehicle conditions, e.g., the parameters of the car (steering, braking and accelerating), vehicle's location, complexity of the environment, and distance from other automobiles. Furthermore, it has been proposed that these systems can also monitor the driver's condition through the recording of physiological signals such as electroencephalography (EEG), electrocardiography (ECG) or electrooculography (EOG) (Chuang et al, 2010;Haufe et al, 2011;Haufe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These BCI systems would decode driver's brain activity to estimate his/her cognitive states or action intentions. For instance, the system can verify whether the driver is paying attention to the driving behavior (Simon et al, 2011), estimate mental workload (Dijksterhuis et al, 2013), or predict driver's intention of action (e.g., braking, traffic lights, and lane changes) (Haufe et al, 2011;Gheorghe et al, 2013;Haufe et al, 2014;Sonnleitner et al, 2014;Kim et al, 2015;Khaliliardali et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The modern research on brake-assisting typically considers the brain and the myoelectric activities measured by electroencephalography (EEG) and electromyography (EMG), respectively [7][8][9]. These approaches demonstrate the high feasibility of predicting the emergency situation on the road.…”
Section: Introductionmentioning
confidence: 99%